Coming to Judgment: Methodological Reflections on the Relationship Between Ecclesiology, Ethnography and Political Theory - Bretherton, Luke (Modern theology, 2012)
This essay theoretically frames the inter-relationship between ecclesial and political life and suggests how the ethnographic study of this intersection might generate theological conceptualisations of both. It argues there is a dialectical relationship between conceptualisations of ecclesial and political life and that their proper study requires attention to practice in order to generate judgments on both. The key issue here is the kind of rationality from which judgments on practice are derived. A case is made for practical reason as having priority over theoretical reason when thinking about politics and the need to move beyond interpretation to judgment.